Common single nucleotide polymorphisms in genes related to immune function and risk of papillary thyroid cancer. - Alina V Brenner; Gila Neta; Erich M Sturgis; Ruth M Pfeiffer; Amy Hutchinson; Meredith Yeager; Li Xu; Cindy Zhou; William Wheeler; Margaret A Tucker; Stephen J Chanock; Alice J Sigurdson (PLoS ONE)
Accumulating evidence suggests that alterations in immune function may be important in the etiology of papillary thyroid cancer (PTC). To identify genetic markers in immune-related pathways, we evaluated 3,985 tag single nucleotide polymorphisms (SNPs) in 230 candidate gene regions (adhesion-extravasation-migration, arachidonic acid metabolism/eicosanoid signaling, complement and coagulation cascade, cytokine signaling, innate pathogen detection and antimicrobials, leukocyte signaling, TNF/NF-kB pathway or other) in a case-control study of 344 PTC cases and 452 controls. We used logistic regression models to estimate odds ratios (OR) and calculate one degree of freedom P values of linear trend (P(SNP-trend) ) for the association between genotype (common homozygous, heterozygous, variant homozygous) and risk of PTC. To correct for multiple comparisons, we applied the false discovery rate method (FDR). Gene region- and pathway-level associations (P(Region) and P(Pathway)) were assessed by combining individual P(SNP-trend) values using the adaptive rank truncated product method. Two SNPs (rs6115, rs6112) in the SERPINA5 gene were significantly associated with risk of PTC (P(SNP-FDR)/P(SNP-trend)= 0.02/6×10(-6) and P(SNP-FDR)/P(SNP-trend)= 0.04/2×10(-5), respectively). These associations were independent of a history of autoimmune thyroiditis (OR = 6.4; 95% confidence interval: 3.0-13.4). At the gene region level, SERPINA5 was suggestively associated with risk of PTC (P(Region-FDR)/P(Region)= 0.07/0.0003). Overall, the complement and coagulation cascade pathway was the most significant pathway (P(Pathway)= 0.02) associated with PTC risk largely due to the strong effect of SERPINA5. Our results require replication but suggest that the SERPINA5 gene, which codes for the protein C inhibitor involved in many biological processes including inflammation, may be a new susceptibility locus for PTC.